Robinson Crusoe - Defoe;Daniel (London Welbeck Editions, 2021)
"Young and impulsive, Robinson Crusoe defies the advice of his parents and runs away to sea. He is plagued by misfortune at every turn; his first ship sinks in a violent storm, his friend and mentor dies, then he is captured by pirates and made a slave in the port of Sallee. Through all these hardships, Crusoe's determination and resourcefulness fills him with hope for a better life, and fate delivers him the opportunity for freedom, friendship and riches. But it is when he is shipwrecked on a deserted island that he faces his greatest test: not simply to survive but to thrive."